On Some Types Of Ideals On Supra Topological Space - Omar S. Mustafa (Al-Qadisiyah Journal of Pure Science, 2018)
This paper introduces some types of ideals on supra topological Space called ∗, ∗∗, ∗& ∗∗, and it is studying the relations among ideal, ∗and ∗∗, ∗& ∗∗, on supra topological spaces .Also introduce a new class of sets and functions between topological spaces called supra ∗- open sets and ∗∗ and supra ∗∗-open sets . Finally investigate some properties between them